PERENCANAAN PENYUSUNAN PAKET PERJALANAN WISATA DI KABUPATEN ROTE NDAO - Manafe, Putry JC (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2019)
This research used a descrictiptive qualitative method with the technique of obtainine information/ taking informants using the purposive sampling technique. Data collection techniques used were the method of observation, interview and documentation studies. Data analysis technique used data reduction, display, and verification or drawing conclusions. The result of this research notes that Rote Ndao District has the potential for natural, cultural and artificial tourism. These tourism potentials can be packaged into tour packages such as: Telaga Nirwana, Mulut Seribu, Oelangga Beach, Bebalain Hill, Raja Kedoh House and Ikat Weaving Center. The concept of indoor and outdoor tour packages are combined into one tour package. Based on these potentials, tour package planning is then made in the form of tables, descriptions and graphs. The tour packages made include 3 Days 2 Nights Rote Tour.